Current debates about dignity and human rights. Legal and philosophical contexts - Benkovska, D.; Kozlovski, R. (Ефективність державного управління, 2017)
Nowadays one can observe many different conceptions of human dignity. Dignity employed in current social, philosophical, medical and bioethical debate, and corresponding legal instruments. It develops a view of human dignity as a foundation of human rights. Placing dignity in axiological order in human rights does not solve all the problems. The question who is a person in the light of human rights still provoke a certain axiological and ethical discourse, in which they wish to engage with their own interpretation of the law, as well as to decide on certain anthropology, from which they acquire a particular concept of a human. Also European jurisprudence is trying to find the right answer to such sensitive question, but the courts left the question open, so the conflict continues.